Cognate Ligand Chaperoning: a Novel Mechanism for the Post-translational Regulation of Neurotransmitter Receptor Biogenesis - Leidenheimer, Nancy J. (Frontiers in Cellular Neuroscience, 2017)
The functional unit for inter-neuronal communication in the central nervous system is the neuronal synapse. The number of postsynaptic neurotransmitter receptors at the cell surface is an important determinant of synaptic efficacy and plasticity. A diverse array of post-translational processes regulate postsynaptic receptor number, including receptor exocytosis, lateral diffusion, surface stabilization, endocytosis, and recycling, thus highlighting the importance of mechanisms that control postsynaptic receptor levels. Another putative post-translational mechanism for regulating receptor surface expression is cognate ligand chaperoning. It has been proposed that neurotransmitters function as cognate ligand chaperones by binding, within the endoplasmic reticulum (ER) lumen, to their nascent neurotransmitter receptors and facilitating receptor biogenesis. Here we discuss proof-of-concept evidence that small molecules can selectively facilitate the biogenesis of their targets and examine the specific evidence in support of cognate ligand chaperoning of neurotransmitter receptor biogenesis.